PENGARUH UKURAN PERUSAHAAN, PROFITABILITAS, DAN KEPEMILIKAN MANAJERIAL TERHADAP INCOME SMOOTHING - Fanny Dwi Oktaviani (2023)
The purpose of this research is to empirically examine the effect of firm size, profitability, and managerial ownership on income smoothing with firm age and leverage as control variables. Income Smoothing is proxied using the Eckel Index. This research is a quantitative research and the objects in this research are manufacturing sector companies listed on the Indonesia Stock Exchange (IDX) for the 2019-2021 period. Selection of sample criteria was carried out by purposive sampling technique with predetermined criteria and obtained data of 282 samples obtained from 94 companies. Testing the hypothesis in this study using multiple linear regression analysis with the help of STATA software version 16. The results of this study indicate that 1) firm size has no effect on income smoothing; 2) profitability has no effect on income smoothing; and 3) managerial ownership has no effect on income smoothing.